2023
DOI: 10.3390/jcm12052024
|View full text |Cite
|
Sign up to set email alerts
|

Neuroworsening in the Emergency Department Is a Predictor of Traumatic Brain Injury Intervention and Outcome: A TRACK-TBI Pilot Study

Abstract: Introduction: Neuroworsening may be a sign of progressive brain injury and is a factor for treatment of traumatic brain injury (TBI) in intensive care settings. The implications of neuroworsening for clinical management and long-term sequelae of TBI in the emergency department (ED) require characterization. Methods: Adult TBI subjects from the prospective Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot Study with ED admission and disposition Glasgow Coma Scale (GCS) scores were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…These findings are consistent with those in the current literature. [38][39][40][41] In these patients at higher risk for death, therapy with UH and LMWH may be especially beneficial despite the risk of increased hospital complications, due to the mortality benefit they confer. Conversely, higher GCS score and, surprisingly, a history of dementia were associated with lower odds of death.…”
Section: Additional Risk Factors Of Mortalitymentioning
confidence: 99%
“…These findings are consistent with those in the current literature. [38][39][40][41] In these patients at higher risk for death, therapy with UH and LMWH may be especially beneficial despite the risk of increased hospital complications, due to the mortality benefit they confer. Conversely, higher GCS score and, surprisingly, a history of dementia were associated with lower odds of death.…”
Section: Additional Risk Factors Of Mortalitymentioning
confidence: 99%
“…Mortality rates that are directly associated with TBI include death resulting from the initial injury in the acute phase, within hours to days of the incident. Research studies have investigated the predictors for immediate impact of TBI on mortality such as the severity of injury, GCS, neuroimaging findings and type of injury [12,13]. For example, studies have shown that subjects with penetrating TBI show higher mortality rates in comparison to blunt TBI [14].…”
Section: Introductionmentioning
confidence: 99%
“…While rates of neurosurgical procedural interventions and mortality are low for GCS 13-15 TBI (3-9% and 1-2%, respectively) [27,28], neurologic deterioration can occur acutely in this population and patients with GCS deficits or intracranial neuroimaging findings should receive vigilant clinical monitoring and treatment [29]. Recent studies have bolstered the recognition of non-"mild" TBI symptomatology and sequelae that compromise the return to baseline function.…”
mentioning
confidence: 99%